2019
DOI: 10.1039/c9ra06132k
|View full text |Cite
|
Sign up to set email alerts
|

Thermal effect of annealing-temperature on solution-processed high-k ZrO2 dielectrics

Abstract: In this paper, a solution-processed zirconium oxide (ZrO2) dielectric was deposited by spin coating with varying pre-annealing temperatures and post-annealing temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The inverse trend between μ h vs N t is also evident as shown in Figure c. From the literature, several reports showed that annealing at 200 °C yields optimal film quality and electrical properties, such as low defects, low leakage current, and an ultrasmooth film surface. ,, A similar trend can also be found in that lower annealing temperatures result in less charge trapping and interface states in oxides. , These findings are in accordance with our AFM and TFT results; the film quality and electrical properties were optimal at the lowest oxide annealing temperature (200 °C in this study). Moreover, AlO x was observed to show the lowest N t due to the smoothest surface, while HfO x was found to be in the opposite.…”
Section: Resultsmentioning
confidence: 96%
“…The inverse trend between μ h vs N t is also evident as shown in Figure c. From the literature, several reports showed that annealing at 200 °C yields optimal film quality and electrical properties, such as low defects, low leakage current, and an ultrasmooth film surface. ,, A similar trend can also be found in that lower annealing temperatures result in less charge trapping and interface states in oxides. , These findings are in accordance with our AFM and TFT results; the film quality and electrical properties were optimal at the lowest oxide annealing temperature (200 °C in this study). Moreover, AlO x was observed to show the lowest N t due to the smoothest surface, while HfO x was found to be in the opposite.…”
Section: Resultsmentioning
confidence: 96%
“…The peak center at 530.3 eV represents the oxygen inside the metallic oxygen ( M –O– M ), at 531.4 eV represents the oxygen in the lattice oxygen vacancy ( V O ), and 532.2 eV represents the oxygen inside the hydroxyl oxygen ( M ‐OH). [ 30 ] For convenience, we used O I , O II , and O III to represent each component area and then calculated the percentages of O I , O II , and O III to the total area of elemental oxygen, respectively, which were used to represent the content of each component, and then summarized the results in Figure 2e. We all know that metal–oxygen bonding ( M –O– M ) is favorable for high‐ k dielectric films, and it can be seen from the figure that the content of metal–oxygen, hydroxyl oxygen, and vacancy oxygen is closely related to the annealing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Doping Zr improves the electrical properties of the films by replacing weak oxygen bonds in AlO x (Al-O (511 kJ•mol −1 ), Zr-O (766.1 kJ•mol −1))[53,54]. For the alumina films, the weak bonds to oxygen construct a loose oxide structure[55]. Thanks to the presence of Zr atoms, the larger atomic size (Ion radius Zr 4+ :Al 3+ = 80:50) leads to the decrease of ion conduction and makes the Zr-AlO x films more densified[19,34].…”
mentioning
confidence: 99%